Cellular and immune landscape of chronic liver diseases: insights from immunophenotyping - Soleimani, Shaghayegh; Albayrak, Ozgur; Somay, Kayra; Yang, Hong; Yigit, Buket; Ulukan, Burge; Atak, Dila; Akyildiz, Murat; Gursoy, Metehan; Demirtas, Elif; Mardinoglu, Adil; Vural, Atay; et al. (Frontiers in Molecular Biosciences, 2025)
BackgroundChronic liver disease due to alcohol-related liver disease and chronic viral hepatitis pose a substantial burden on healthcare systems. Chronic liver disease may predispose to hepatocellular carcinoma, for which therapeutic options are limited. This study aimed to explore the immune cell characteristics of the clinical conditions.MethodsExplant liver samples were collected from 25 patients for bulk RNA sequencing and flow cytometry analysis. Immune cell populations were characterized by flow cytometry from isolated hepatic and peripheral mononuclear cells.ResultsSignificant differences in immune cell characteristics were observed among patients with three clinical conditions. Viral hepatitis and peri-tumor samples exhibited higher hepatic B cell counts compared to alcohol-related liver disease. Additionally, chronic liver disease patients showed higher levels of CD57+ T cells, suggestive of T cell differentiation. Differential expression analysis identified several genes associated with immune regulation, including downregulation of CD27 and upregulation of granzyme B in ARLD, consistent with a highly differentiated phenotype. LAG3 and PDCD1 were upregulated in peri-tumor samples. The NK cell count was lower in peri-tumor liver specimens compared to ARLD, and an upregulation of TIGIT, an inhibitory marker, was observed in those peri-tumor specimens.ConclusionThis study contributes to the understanding of immune dynamics in chronic liver disease among different etiologies. B lymphocytes are relatively reduced in alcohol-related liver disease compared to other groups, and T cells exhibit a more differentiated subtype. The peritumor microenvironment in HCC suggests a relatively diminished presence of NK cells and a potential tendency toward increased inhibitory characteristics.